Effect of perchlorate ion within the polypyrrole matrix on the electrooxidation of ethylene glycol in acidic media. - Becerik, I. (My University, 2002)
The electrooxidation of ethylene glycol was investigated on platinum and perchlorate ions doped polypyroole film electrodes in acidic media. The presence of perchlorate ion was observed by XPS experiments. Optimum experimental conditions were determined. The electrooxidation kinetic of ethylene glycol was studied as a function of ethylene glycol concentration, potential scan limit and scan rate. Results suggest that the doping process has a strong effect on the oxidation reaction.
Keywords: Ions; Ethylene Glycol; Perchlorates; Polymers; Spectrophotometry; Electrochemistry; Pyrroles; Hydrogen-Ion Concentration; Oxidation-Reduction; Sodium Compounds